ANALISIS SWOT D’VUL RERSTAURANT AND CAFE DI LOMBOK INTERNATIONAL AIRPORT DALAM UPAYA MENDUKUNG PENGHARGAANWORLD’S BEST HALAL HONEYMOON DESTINATION AND WORLD’S BEST HALAL TOURISM DESTINATION - muhammad habibullah aminy (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
SWOT analysis is one way to determine the business strategy used for planning, organizing, actuating, and controlling (POAC) business strategies in the long and short term. From the description above, the researcher tried to examine the